Effects of Different Drying on Chemical Composition, Antioxidant Activity, and Sensory Evaluation of Cassia Senna Tea Leaves (Cassia angustifolia Vahl.) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study aims to investigate the chemical composition, antioxidant activity, and sensory evaluation of Cassia angustifolia Vahl. tea leaves processed using two drying methods: cabinet (at 80°C) and freeze-drying. The research focuses on evaluating the impact of different drying methods on proximate composition, including carbohydrates, protein, and fat, as well as the presence of bioactive compounds such as phenolics and flavonoids, which are closely linked to antioxidant properties. It’s also highlighting vitamin C content and free radical inhibition capacity, assessed through DPPH and ABTS assays. The findings reveal that freeze-drying preserved higher bioactive content, as observed in the vitamin C analysis and the total phenolic and flavonoid content (1.10%, 311.76 mg GAE/g, and 372.70 mg QE/g, respectively) compared to cabinet drying, which resulted in a loss of these compounds due to high temperatures. These compounds are strongly correlated with antioxidant activity, as demonstrated in both free radical inhibition tests (DPPH and ABTS assays). Freeze-dried tea exhibited higher antioxidant activity in both assays (67.76% for DPPH and 57.71% for ABTS) compared to cabinet-dried tea (50.74% for DPPH and 44.71% for ABTS) at a concentration of 250 mg/L. The antioxidant tests confirmed significant free radical inhibition activity in Cassia angustifolia tea, highlighting its potential as a natural antioxidant source. However, sensory evaluation revealed that panellists preferred tea made from cabinet-dried leaves in terms of colour, taste, and overall quality, emphasizing the importance of processing methods in determining sensory attributes.
Keywords: Cassia angustifolia; Cabinet drying; Freeze drying; Antioxidant activity; Sensory evaluation